miR-205-5p Mediated Downregulation of PTEN Contributes to Cisplatin Resistance in C13K Human Ovarian Cancer Cells - Shi, Xiaoyan; Xiao, Lan; Mao, Xiaolu; He, Jinrong; Ding, Yu; Huang, Jin; Peng, Caixia; Xu, Zihui (Frontiers in Genetics, 2018)
Cisplatin resistance is a major cause of treatment failure in advanced ovarian cancer. The limited evidence shows the paradoxical regulation of miR-205 on chemotherapy resistance in cancer. Herein, we found that miR-205-5p was enormously increased in cisplatin-resistant C13K ovarian cancer cells compared with its cisplatin-sensitive OV2008 parental cells using miRNA microarrays, which was further verified by quantitative PCR. Furthermore, we confirmed that inhibition of miR-205-5p upregulated PTEN and subsequently attenuated its downstream target p-AKT, which inversed C13K cells from cisplatin resistance to sensitivity. Our data suggest that miR-205-5p contributes to cisplatin resistance in C13K ovarian cancer cells may via targeting PTEN/AKT pathway.